2023
DOI: 10.3390/biom13040691
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Receptor Gene Variants Underlying Disorders/Differences of Sex Development through Abnormal Testicular Development

Abstract: Gonadal development is the first step in human reproduction. Aberrant gonadal development during the fetal period is a major cause of disorders/differences of sex development (DSD). To date, pathogenic variants of three nuclear receptor genes (NR5A1, NR0B1, and NR2F2) have been reported to cause DSD via atypical testicular development. In this review article, we describe the clinical significance of the NR5A1 variants as the cause of DSD and introduce novel findings from recent studies. NR5A1 variants are asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 132 publications
0
10
0
Order By: Relevance
“…COUP-TFs are members of the steroid/thyroid hormone receptor superfamily. COUP-TF homologs, which have been cloned from humans, suggest that their protein sequences are highly homologous across species, defining functional conservation ( 62 , 78 ). NR2F2 is primarily expressed in mesenchymal cells ( 78 ).…”
Section: Molecular Etiologies Of 46xx T-dsd and Ot-dsdmentioning
confidence: 99%
See 4 more Smart Citations
“…COUP-TFs are members of the steroid/thyroid hormone receptor superfamily. COUP-TF homologs, which have been cloned from humans, suggest that their protein sequences are highly homologous across species, defining functional conservation ( 62 , 78 ). NR2F2 is primarily expressed in mesenchymal cells ( 78 ).…”
Section: Molecular Etiologies Of 46xx T-dsd and Ot-dsdmentioning
confidence: 99%
“…In developing testicular tissue, NR2F2 expression is observed in Leydig cells from 7 to 10 gw but is downregulated at 15 gw and repressed throughout fetal life. Previous studies concluded that NR2F2 repression is important for fetal Leydig cell differentiation ( 62 ). According to rodent studies, the target genes of NR2F2 in Leydig cells are AMHR2 , INSL3 , and genes encoding steroidogenic enzymes ( 62 ).…”
Section: Molecular Etiologies Of 46xx T-dsd and Ot-dsdmentioning
confidence: 99%
See 3 more Smart Citations